Nilai-Nilai Pendidikan Multikultural dalam Al Qur’an: Kajian terhadap Tafsir Al-Azhar Karya Buya HAMKA - Firman, Firman (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2016)
Quran is life guidance and there is no doubt about it, it is also as a guidance of all human life problems in this world, including problems of multicultural conflicts which occur in the society. Quran which consists of 30 juz 114 surah has explored humanistic principles and values in the interaction to other humans both of in group and inter group interaction need to be studied in order to solve all problems occurs in the society. Problems of this research are: (1) How are main themes of multicultural education values in tafsir Al-Azhar by Buya Hamka? (2) How is the perspective of Buya Hamka towards multicultural education values in tafsir Al-Azhar. This is a library research. Data collection technique is by using documents, the researcher collected and reviewed books, kitab, journals, and other writing materials which are connected to multicultural education and came up with the description. Data of this research was analyzed by using linguistics, sociological, and theological approach. Buya Hamka in interpreting verses about multicultural emphasizes on the concept of unity and similarity. According to Hamka, diversity is a starting points of the conflicts in the life of society. Unity and similarity concept by Buya Hamka can be viewed from two points. They are: (1) Unity and similarity of human origins from the same father and mother. (2) Unity and similarity of aqidah to make human becomes brothers and sisters.